Increasing Fluroquinolone Susceptibility and Genetic Diversity of ESBL-Producing E. coli from the Lower Respiratory Tract during the COVID-19 Pandemic - Katja Hrovat; Katja Seme; Jerneja Ambrožič Avguštin (MDPI AG, 2024)
Lower respiratory tract infections (LRTIs) are the fourth leading cause of death worldwide, among which Escherichia coli (E. coli) pneumonia is considered a rare phenomenon. Treatment options for LRTIs have become limited, especially for extended-spectrum β-lactamase-producing E. coli (ESBL-EC), which are usually resistant to other groups of antimicrobials as well. The aim of our study was to compare the phenotypic resistance profiles and genotypes of ESBL-EC isolates associated with LRTIs before (pre-COVID-19) and during (COVID-19) the COVID-19 pandemic. All isolates were screened for antimicrobial resistance genes (ARGs) and virulence-associated genes (VAGs) and assigned to phylogenetic groups, sequence types and clonal groups by PCR. During the pandemic, a significantly lower proportion of ciprofloxacin-, levofloxacin- and trimethoprim-sulfamethoxazole-resistant ESBL-EC isolates was retrieved from lower respiratory tract (LRT) samples. PCR-based genotypization revealed greater clonal diversity and a significantly lower proportion of isolates with blaTEM, aac(6')-Ib-cr and qacEΔ1 genes. In addition, a higher proportion of isolates with the integrase gene int1 and virulence genes sat and tsh was confirmed. The lower prevalence of fluoroquinolone resistance and greater genetic diversity of ESBL-EC isolated during the COVID-19 period may have been due to the introduction of new bacterial strains into the hospital environment, along with changes in clinical establishment guidelines and practices.